Return to me : a biblical theology of repentance - Boda, Mark J. (Downers Grove, Illinois : InterVarsity Press, 2015)
"The theme of repentance is evident in almost every Old and New Testament corpus. However, it has received little sustained attention over the past half-century of scholarship, which has been largely restricted to word studies or focused on a particular text or genre. Studies of the overall theology of the Bible have typically given the theme only passing mention. In response, Mark Boda offers a comprehensive overview of the theological witness of Scripture to the theme of repentance. The key to understanding is not simply to be found in word studies, but also in the broader meaning of texts as these communicate through a variety of words, images and stories. The importance of repentance in redemptive history is emphasized. It is fundamentally a return to intimate fellowship with the triune God, our Creator and Redeemer. This relational return arises from the human heart and impacts attitudes, words and actions."--Back cover.
1. Introduction. Defining biblical theology ; Defining our biblical-theological topic ; Past research on the biblical theology of repentance -- 2. Repentance in the torah. Genesis ; Exodus ; Leviticus ; Numbers ; Deuteronomy ; Summary -- 3. Repentance in the former prophets. Joshua ; Judges ; Samuel ; Kings ; Summary -- 5. Repentance in the latter prophets : penitential process -- 5. Repentance in the latter prophets : Isaiah. Isaiah 1-39 ; Isaiah 40-55 ; Isaiah 56-66 ; Summary -- 6. Repentance in the latter prophets : Jeremiah and Ezekiel. Jeremiah ; Jeremiah 1-23 ; Jeremiah 26-52 ; Ezekiel ; Ezekiel 4-33 ; Ezekiel 33-48 -- 7. Repentance in the latter prophets : the twelve. Hosea ; Joel ; Amos ; Jonah ; Micah ; Nahum-Zephaniah ; Haggai ; Zechariah ; Malachi ; Summary -- 8. Repentance in the writings : wisdom and worship. Job ; Proverbs ; Psalms ; Summary -- 9. Repentance in the writings : exile and restoration. Lamentations ; Daniel ; Ezra-Nehemiah ; Summary -- 10. Repentance in the writings : chronicles. David as exemplary penitent (1 Chr. 21) ; Solomon as promoter of repentance (2 Chr. 6-7) ; Solomon's penitential vision realized (2 Chr. 10-36) ; Summary -- 11. Repentance in Old Testament theology. Dimensions of repentance ; Motivation of repentance ; Purpose of repentance ; Sociology of repentance ; Psychology of repentance ; Divine disablement ; Divine enablement ; Repentance in redemptive history : exile and restoration ; Conclusion -- 12. Repentance in the New Testament. Synoptic gospels and Acts ; Gospel of John ; Epistles ; Revelations ; Summary -- 13. Repentance in New Testament theology. Repentance in redemptive history : restoring the kingdom ; Dimensions of repentance ; Motivation for repentance ; Purpose of repentance ; Sociology of repentance ; Psychology of repentance ; Divine disablement ; Divine enablement ; Conclusion -- 14. Theological implications of repentance. Beginning the journey ; Continuing the journey.
Includes bibliographical references (pages 199-212) and indexes.
Keywords: Repentance -- Biblical teaching; Bible -- Theology